Optically stimulated luminescence of alexandrite - Nunes, Matheus C.S. [UNESP]; Trindade, Neilo M.; Yoshimura, Elisabeth M.; Chithambo, Makaiko L. (Elsevier, 2024)
We report the optically stimulated luminescence (OSL) of natural alexandrite (BeAl2O4:Cr3+) from Brazil. Luminescence was stimulated using 470 nm blue, 525 nm green and 850 nm infrared light. The dose-response of the OSL is linear in all cases, a desirable feature of dosimetry applications. The influence of preheating on OSL suggests that electron traps associated with the thermoluminescence of alexandrite contribute to the OSL. Mechanisms responsible for luminescence in alexandrite have been briefly considered.
Keywords: Alexandrite; Dosimetry; Ionizing radiation; Light-emitting diodes; Optically stimulated luminescence